Endoscopic retrograde cholangiopancreatography for biliary system parasites - Yılmaz, Sezgin (Turk J Surg, 2018)
OBJECTIVE: Endoscopic retrograde cholangiopancreatography may be useful in the diagnosis and management of biliary system parasites. MATERIAL AND METHODS: Investigators retrospectively evaluated patients with biliary system parasites who underwent endoscopic retrograde cholangiopancreatography procedures over an eight-year period. We collected data regarding patient demographics, clinical features, and parasite type. We aimed to determine the utility of endoscopic retrograde cholangiopancreatography as a diagnostic and therapeutic intervention in patients with biliary system parasites. RESULTS: We identified 22 patients with biliary system parasites from a total of 3,450 endoscopic retrograde cholangiopancreatography procedures performed during an eight-year period. Parasite types included Echinococcus granulosus (n=19), Fasciola hepatica (n=2), and Ascaris lumbricoides (n=1). Fifteen patients with liver hydatid cysts underwent endoscopic retrograde cholangiopancreatography prior to surgery due to obstructive jaundice. The endoscopic retrograde cholangiopancreatography procedure enabled definitive treatment without the need for surgery in the remaining two patients. Two patients with fascioliasis underwent endoscopic retrograde cholangiopancreatography due to clinical presentation of cholangitis, cholecystitis, and obstructive jaundice, leading to presumptive diagnosis of cholangiocarcinoma. However, the final diagnosis was made using endoscopic retrograde cholangiopancreatography following inspection of flat, leaf-shaped, motile flukes extracted from the bile duct. In one patient with ascariasis, a longitudinal tubular structure was identified in the bile duct; emergency surgery was required. CONCLUSION: The diagnosis of parasitic diseases is clinically challenging, and definitive diagnosis requires endoscopic retrograde cholangiopancreatography in some cases. Moreover, endoscopic retrograde cholangiopancreatography provides a therapeutic option for ascariasis, fascioliasis, and some forms of hydatidosis. Accordingly, the use of endoscopic retrograde cholangiopancreatography may change preoperative management and treatment strategies for biliary system parasite infections.